Zinc fertilization approaches for agronomic biofortification and estimated human bioavailability of zinc in maize grain. Issue 1 (2nd January 2017) - Imran, Muhammad; Rehim, Abdur
ABSTRACT: Maize ( Zea mays L.) is generally low in bioavailable zinc (Zn); however, agronomic biofortification can cure human Zn deficiency. In the present experiment, Zn was applied in pots as ZnSO4 · 7H2 O to maize cultivar DK-6142 as foliar spray (0.5% w/v Zn sprayed 25 days after sowing and 0.25% w/v at tasseling), surface broadcasting (16 kg Zn ha − 1 ), subsurface banding (16 kg Zn ha − 1 at the depth of 15 cm), surface broadcasting + foliar and subsurface banding + foliar in comparison to an unfertilized control. As compared to control, all treatments significantly ( P ≤ 0.05) increased growth, yield and nutritional attributes in maize. Grain Zn and protein concentrations were correlated and ranged from 22.3 to 41.9 mg kg −1 and 9 to 12 %, respectively. Zinc fertilization also significantly reduced grain phytate and increased grain Zn concentration. Zinc fertilization, especially broadcasting and subsurface banding combined with foliar spray decreased grain [phytate]:[Zn] ratio to 28 and 21 and increased Zn bioavailability by trivariate model of Zn absorption to 2.04 to 2.40, respectively. Conclusively, broadcasting and subsurface banding combined with foliar spray is suitable for optimal maize yield and agronomic Zn biofortification of maize grain. This would also be helpful to optimize Zn and protein concentration in maize grain.